2018
DOI: 10.1016/j.cell.2018.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Protein Thermal Stability Variation during the Cell Cycle

Abstract: SummaryQuantitative mass spectrometry has established proteome-wide regulation of protein abundance and post-translational modifications in various biological processes. Here, we used quantitative mass spectrometry to systematically analyze the thermal stability and solubility of proteins on a proteome-wide scale during the eukaryotic cell cycle. We demonstrate pervasive variation of these biophysical parameters with most changes occurring in mitosis and G1. Various cellular pathways and components vary in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
220
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(257 citation statements)
references
References 71 publications
15
220
0
Order By: Relevance
“…Several reports have indicated differential stability of the two proteasome subunits (Mathieson et al , ). Becher et al () used a thermal proteome profiling strategy by MS and reported that during the cell cycle the proteasome showed a different stability and abundance variation in a protein subset of the 19S regulatory sub‐complex. Using a similar approach, Volkening et al () reported that the regulatory 19S complex has much lower protein melting temperature and a higher degree of conformation flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated differential stability of the two proteasome subunits (Mathieson et al , ). Becher et al () used a thermal proteome profiling strategy by MS and reported that during the cell cycle the proteasome showed a different stability and abundance variation in a protein subset of the 19S regulatory sub‐complex. Using a similar approach, Volkening et al () reported that the regulatory 19S complex has much lower protein melting temperature and a higher degree of conformation flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal proximity co-aggregation (TPCA) has demonstrated promise for interrogating protein interaction networks in vivo , or across distinct cellular states [65][66][67] , but to date has been limited to monitoring the dynamics of known interactions or protein complexes, rather than enabling de novo network inference. In contrast, the primary disadvantage associated with SEC-PCP-SILAC is its moderate bias towards proteins of greater cellular abundance [68] .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the perturbations can be applied in a dose‐dependent manner (Becher et al , ) or time‐dependent manner (Becher et al , ; Dai et al , ) to improve data analysis or facilitate mechanistic understanding of the perturbation (Fig ). Using this approach, it has been possible to deconvolute drug targets (Savitski et al , , ; Huber et al , ; Reinhard et al , ; Becher et al , ; Mateus et al , , ; Kitagawa et al , ; Azimi et al , ; Hu et al , ) and enzyme substrates (preprint: Saei et al , ), study metabolic shifts (Becher et al , ; Dai et al , ; Mateus et al , ), or identify protein–protein interactions (Tan et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the eukaryotic RNA polymerase II (POLR2A/B) shows a biphasic melting behavior that is only visible in the melting profile, and that reflects the presence of two sub‐populations: one with a higher melting point that is bound to DNA and actively transcribes it, and one that is less thermostable because it is not bound to DNA. The latter is more prevalent during mitosis, when there is a general transcriptional arrest (Becher et al , ).…”
Section: Introductionmentioning
confidence: 99%